Acid Hydrolysis of Bromazepam Catalyzed by Micelles, Reverse Micelles, and Microemulsions - Ferdousi Begum; M. Yousuf A. Mollah; M. Muhibur Rahman; Md. Abu Bin Hasan Susan (Journal of Chemistry)
Kinetics of the acid hydrolysis of bromazepam (Bz) has been investigated in micelles, reverse micelles, and microemulcions of cetyltrimethylammonium bromide (CTAB) by spectrophotometric method. The rate of the acid hydrolysis of Bz was found to be enhanced both below and above the critical micelle concentration (CMC) of CTAB in aqueous solution. The pseudo-first-order rate constant (k′) shows an initial decrease for both low and high H+ concentrations. With further increase in [CTAB], at low [H+], the k′ attains an almost constant value, while, at high [H+], the k′ passes through a maximum and then decreases. The kinetic data for catalysis by micelles of CTAB was interpreted with the pseudophase ion exchange (PIE) model. In CTAB/cyclohexane/1-butanol/water microemulsions, as the water to surfactant ratio (wo) increases, the physicochemical properties and droplet sizes of microemulsions significantly change and distinct changes in reaction environment can be marked. The rate of the hydrolysis reaction exhibits excellent correlation with the physicochemical properties and droplet sizes of the microemulsions and reverse micelles of CTAB. At [H+] = 0.001 M, in reverse micelles and microemulsions of CTAB, the k′ of the acid hydrolysis of Bz decreases sharply followed by a slight increase with increasing wo.